PENERAPAN PRINSIP EQUALITY BEFORE THE LAW DALAM PERLINDUNGAN HAK ASASI MANUSIA (HAM) TERKAIT KHALWAT JINAYAH YANG BERLAKU DI ACEH - Arisandhi Safana; Mohammad Eka Putra; Chairul Bariah; Mirza Nasution (Smart Education, 2024)
Abstract: Human rights are natural rights that are inherent from the moment humans are born, one of which is the right to equal status before the law, the fulfillment of which is mandatory for the state and the entire community. Aceh is one of the special regions where Islamic sharia qanuns are implemented, including the provisions on ikhtilath and adultery therein. In its application, it often becomes a contradiction when one party admits to having committed adultery while the other party does not confess, even though the crime in q uestion was committed jointly with the same tempus and locus delicti. The method used in this research is normative juridical with analytical descriptive characteristics which are collected using literature study techniques and analyzed using qualitative data analysis methods. The results of the research found that there was inequality before the law, That is state violated human rights by omission by not fulfilling the principle of non-derogable rights, so there was a need for a judicial review of the Aceh Qanun that was more dynamic and in line with current developments, judges in this case should be able to determine justice as it should be, is not only a mouthpiece for the law, but is obliged to explore, follow and understand the values that live in society. Keywords: equality before the law, human rights, khalwat jinayah and qanun. Abstrak: Hak Asasi Manusia merupakan hak kodrati yang melekat sejak manusia dilahirkan, salah satunya hak dalam kedudukan yang sama di mata hukum di mana pemenuhannya wajib dilakukan negara dan seluruh masyarakat. Aceh ialah salah satu daerah istimewa dengan penerapan qanun syariat Islam, termasuk ketentuan ikhtilath dan zina didalamnya. Dalam penerapannya seringkali menjadi kontradiksi manakala satu pihak mengaku telah melakukan perzinahan sedang pihak satunya lagi tidak mengaku, padahal tindak pidana dimaksud dilakukan secara bersama dengan tempus dan locus delicti yang sama. Metode yang digunakan dalam penelitian ini adalah yuridis normatif dengan sifat Deskriptif Analitis yang dikumpulkan dengan teknik studi pustaka dan dianalisis dengan metode analisis data kualitatif. Hasil penelitian menemukan bahwa terjadinya inequality before the law, negara melakukan pelanggaran hak asasi manusia by ommision dengan tidak dipenuhinya asas non derogable rights, sehingga perlu uji materi Qanun Aceh yang lebih dinamis dan sesuai dengan perkembangan zaman, hakim dalam hal ini seharusnya dapat menentukan keadilan sebagaimana seharusnya, tidak hanya sebagai corong undang-undang, melainkan wajib menggali, mengikuti, dan memahami nilai yang hidup di masyarakat. Kata kunci: kedudukan yang sama dimata hukum, ham, khalwat jinayah dan qanun.